Peran Aktor dalam Mengatasi Dampak Aktivitas Truk Pengangkut Sampah di Dukuh Promasan, Kota Salatiga - Nofita Natalia; Suryo Sakti Hadiwijoyo; Antik Tri Susanti (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study analyzes how actors and structures play roles in addressing environmental issues caused by waste transportation truck activities in Dukuh Promasan, Salatiga. The findings reveal that the local community is actively involved in collective efforts, such as cleaning the roads and reporting issues related to waste management. Although the community generally tends to be passive towards government policies, this research found that residents of Dukuh Promasan actively participate in mitigating the negative impacts of waste transportation, including problems related to noise, odor, scattered waste, and leachate. The study employs a qualitative descriptive method to examine the interactions among various actors, such as the Environmental Agency (Dinas Lingkungan Hidup), the Ngronggo landfill management, truck drivers, and the Dukuh Promasan community. It explores the social dynamics resulting from these interactions, particularly how community initiatives can influence waste management policies and practices. Moreover, the study identifies the challenges faced by the Environmental Agency in managing waste, such as limited funding and facilities, which negatively affect the efficiency of waste collection and processing. These findings highlight the necessity of policies that promote active community participation in waste management. This research is expected to provide insights into the relationship between community behavior and the waste management system, and to recommend a collaborative approach to enhance environmental sustainability in Dukuh Promasan.